Metode Glenn Doman Meningkatkan Kemampuan Interaksi Sosial Anak Autis - Aydillah, Desy; Rokhaidah, Rokhaidah (Universitas Tribhuwana Tunggadewi, 2018)
ABSTRACT Autism is a complex developmental disorder typically arises during the first three years of life, with one of its characteristics being a disorder of social interaction. This study was conducted to determine the effectiveness of Glenn Doman Method on the ability of social interaction of children with autism. This research uses experimental quasi research design with disign approach one group pretest posttest design. The sample used were 15 autistic children with total sampling technique. Data were analyzed by T-dependent test. The result of statistical analysis shows p value 0,000 (0,000